(untitled) (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2020)
Seagrass known as Lamun in Bahasa is one of the species that are can live in submerged marine habitats. Seagrasses have an important role in the ecosystems, including as primary producers, living habitats of benthic organisms, stabilize bed sediments and carbon storage in shallow-water coastal. Monospecies community of seagrass was found in Malang, however, only limited number studies of seagrass have been done in the area. This study aimed to determine the growth rate and biomass of the seagrass, as well as the phytochemical compounds. Experiments were conducted during August-November in 2014 and 2015. Measurement of in situ growth and biomass leaf were made using marking techniques in one week also the data of leaf seagrass collected were using a random sampling method. Extracted materials were tested by methanol to get the phytochemical compound. Data were analyzed at the Fisheries and Marine Exploration Laboratory, FPIK-UB. The results of the present study showed that two species of seagrass, Syringodium isoetifolium at Kondang Merak and Thalassia hemprichii at Bale Kambang. The growth rate of the seagrass leaves of the former species had positive values with 0.45±0.19 cm/day, hile the later species had 0.25±0.14 cm/day. Furthermore, the biomass value of the two types seagrass obtained that in the below-ground was higher than the above-ground. Phytochemical tests showed that both of type seagrass contained bioactive compounds such as flavonoids and saponins.